Therapeutic Effects of Anti–Bone Morphogenetic Protein and Activin Membrane‐Bound Inhibitor Treatment in Psoriasis and Arthritis. Issue 9 (30th July 2020) - Alvarez, Pilar; Augustín, Juan Jesús; Tamayo, Esther; Iglesias, Marcos; Acinas, Olga; Mendiguren, María Angeles; Vázquez, José Andrés; Genre, Fernanda; San Segundo, David; Merino, Jesús; Merino, Ramón
Abstract : Objective: The transforming growth factor β (TGFβ) inhibitor BAMBI (bone morphogenetic protein and activin membrane‐bound inhibitor) has been shown to control differentiation of CD4+ T lymphocytes into either tolerogenic Treg cells or pathogenic Th17 cells, through the regulation of TGFβ and interleukin‐2 (IL‐2) signaling strength. The present study was undertaken to explore the potential beneficial effects of this strategy of pharmacologic inhibition using novel anti‐BAMBI monoclonal antibodies (mAb) in different experimental murine models of chronic skin and joint inflammatory/autoimmune disease. Methods: Development of Saccharomyces cerevisiae mannan–induced psoriatic arthritis (MIP) (n = 18–30 mice per group), imiquimod‐induced skin psoriasis (n = 20–30 mice per group), or type II collagen–induced arthritis (CIA) (n = 13–16 mice per group) was analyzed in a total of 2–5 different experiments with either wild‐type (WT) or BAMBI‐deficient B10.RIII mice that were left untreated or treated with mAb B101.37 (mouse IgG1 anti‐BAMBI), a mouse IgG1 anti‐TNP isotype control, anti‐CD25, or anti‐TGFβ mAb. Results: Treatment of normal mice with IgG1 anti‐BAMBI mAb clone B101.37 led to expansion of Treg cells in vivo, and had both preventive and therapeutic effects in mice with MIP (each P < 0.05 versus controls). The conferred protection against disease progression was found to be mediated by Treg cells, which controlled the activation and expansion of pathogenic IL‐17–producing cells, and was dependent on the level of TGFβ activity. Furthermore, treatment with B101.37 mAb blocked both the development of skin psoriasis induced by imiquimod and the development of CIA in mice (each P < 0.05 versus controls). Finally, pharmacologic inhibition of BAMBI with the IgM anti‐BAMBI mAb B143.14 also potentiated the suppressive activity of Treg cells in vitro ( P < 0.001 versus controls). Conclusion: These results in murine models identify BAMBI as a promising new therapeutic target for chronic inflammatory diseases and other pathologic conditions modulated by Treg cells.